Role of manganese on the structure, crystallization and sintering of non-stoichiometric lithium disilicate glasses - Gaddam, Anuraag (2017)
The structural role of Mn was investigated in a relatively simple non-stoichiometric lithium disilicate (Li2Si2O5) based glass composition. Glasses were prepared by partially replacing SiO2 by MnO2 from the base glass belonging to the system Li2O-K2O-Al2O3-SiO2. An overall depolymerization of the glass network was observed according to magic angle spinning nuclear magnetic resonance (MAS-NMR) and Fourier transform infrared (FTIR) spectroscopic studies, suggesting a network modifier role for Mn. However, thermal analysis, phase segregation and nucleation in the glasses suggested that Mn might also act as network former. Moreover, calculated crystal field parameters from UV-Visible spectroscopy, showing high ligand field strength (Do) and Racah inter electronic repulsion (B) indicate the possible existence of Mn as individual molecular entities in the interstitials of the glass network. This paper discusses the implications of this structural role of Mn on the crystallization of bulk glasses and on the sintering behaviour and crystallization of glass powder compacts.